MiR‐206 inhibits thyroid cancer proliferation and invasion by targeting RAP1B. Issue 11 (27th June 2019) - Wang, Peng; Gu, Jialei; Wang, Kejing; Shang, Jinbiao; Wang, Wendong
Abstract: Thyroid cancer (TC) is one of the primary tumors arisen from endocrine system. The purpose of this study was to investigate the underlying mechanism by which RAP1B (Ras‐related protein Rap‐1b) modulates microRNA (miR)‐206 related effects on TC cells. Expression of miR‐206 and RAP1B was analyzed in cells and tissues. miR‐206 mimics or inhibitors and RAP1B vector were used in functional experiments to investigate the effects of miR‐206 and RAP1B on cell activities including proliferation, migration, and invasion. Luciferase assay was performed to explore the association between miR‐206 and RAP1B. The influence of miR‐206 on tumorigenesis of TC cells was investigated using an ex vivo model. Our results demonstrated the reduce of miR‐206 in TC tissues and cell lines in which RAP1B was increased. Overexpression of miR‐206 significantly inhibited the functional capacities of TPC‐1 cells including proliferation, invasion, and migration, most likely, through reducing the expression of RAP1B. Xenograft experiment showed that increased miR‐206 could effectively inhibit the tumorigenesis of TC cells. Our study showed that miR‐206 negatively regulated cell activities of proliferation, invasion, and migration in TC via suppressing RAP1B expression, suggesting that miR‐206 exerts a vital role in TC.